Image recognition using Artificial Immune systems approach - Hasnah, Ahmad; Puteh, Saad (Universiti Malaysia Sabah, 2009)
Organized by School of Engineering and Information Technology, Universiti Malaysia Sabah, 3rd - 5th August 2004, Kota Kinabalu, Sabah, Malaysia.